Early and mid-term outcomes of thoracic endovascular aortic repair to treat aortic rupture in patients with aneurysms, dissections and trauma. (15th February 2022) - Benk, Julia; Siepe, Matthias; Berger, Tim; Beyersdorf, Friedhelm; Kondov, Stoyan; Rylski, Bartosz; Czerny, Martin; Kreibich, Maximilian
Abstract: OBJECTIVES: The aim of this study was to analyse outcomes of thoracic endovascular aortic repair to treat aortic rupture. METHODS: Patient and outcome characteristics of all emergent endovascular treatments for thoracic aortic rupture between January 2009 and December 2019 were analysed. RESULTS: Thoracic aortic rupture occurred in patients with aortic aneurysms ( n = 42, 49%), aortic dissection ( n = 13, 16%) or after trauma ( n = 30, 35%). Preoperative cerebrospinal fluid drainage was placed in 9 patients (11%) and 18 patients (21%) underwent perioperative supra-aortic transposition. The proximal landing zones were: zone 1 ( n = 1, 1%), zone 2 ( n = 23, 27%), zone 3 ( n = 52, 61%) and zone 4 ( n = 9, 11%). Temporary spinal cord injury occurred in 1 patient (1%), permanent spinal cord injury in 7 patients (8%). Two patients (2%) experienced a postoperative stroke. Seventeen patients (20%) expired in-hospital. Aortic dissection (odds ratio: 16.246, p = 0.001), aneurysm (odds ratio: 9.090, P = 0.003) and preoperative shock (odds ratio: 4.646, P < 0.001) were predictive for mortality. Eighteen patients (21%) required a stent-graft-related aortic reintervention for symptomatic supra-aortic malperfusion ( n = 3, 4%), endoleaks ( n = 6, 7%), a second aortic rupture ( n = 4, 5%), retrograde type A aortic dissection ( n = 2, 2%), aortic-oesophageal fistulation ( n = 2, 2%) and stent-graft kinking ( n = 1, 1%). CONCLUSIONS: Thoracic endovascular aortic repair in patients with aortic rupture has become a valuable treatment modality to stabilize patients. However, a significant risk of postoperative morbidity and mortality remains, particularly in patients with aortic dissections, aneurysms or shock. Patients require thorough follow-up ideally in an aortic clinic with a staff having the entire spectrum of cardiovascular and thoracic surgical expertise. Abstract : Rupture of the thoracic aorta is one of the gravest emergencies in vascular surgery.